# graph y - 3 = 3(x + 1)

*print*Print*list*Cite

### 3 Answers

y - 3 = 3(x + 1)

first turn this into a Y= mx+b form

y=3X+3+3

y= 3x+6

the slope, or m, in this case, 3, is always rise/run, so rise 3 run 1 from the y-intercept 6, so start at 6, then go up 3 spaces, and over one space, and place a dot, from that dot go up three spaces and then over one and create your line.

### Hide Replies ▲

y - 3 = 3(x + 1) or y=3x+6

i just figured out how to graph..so here is what this would look like

Rewrite the following equation: y - 3 = 3(x + 1)

- Add 3 to both sides. `y=3(x+1)+3`
- Distribute the 3 to x+1. `y=3(x)+3(1)+3`
- Simplify. `y=3x+6`

Based on the `y=mx+b`

- m stands for slope. In this case, m=3
- b stands for y-intercept. In this case, b=6

Graph the y-intercept first. [It should just be a point at (0,6)]. Then, using the slope and do rise/run. In this case, it is 3/1 or... 3 up and 3 down. You can stop after you find the point or you can continue until you feel like stopping. No matter what, the equation is linear and will ALWAYS be a straight line. So, if it becomes crooked for any reason, there was an error & that need to be fixed. In the end, the equation should be graphed as

### Hide Replies ▲

3 up and 1 right OR 3 down and 1 left *

We have to plot graph of the function y-3=3(x+1). Let us write function as,

y=3+3x+3

=> y=3x+6 (i)

It intersects x- axis at x= -2 and y axis at y=6. It will represent a straight line which passes through (-2,0) and (0,6).